Hydration testing of athletes - Oppliger, R. A.; Bartok, C. (Sports Medicine, 2002)
Dehydration not only reduces athletic performance, but also places athletes at risk of health problems and even death. For athletes, monitoring hydration has significant value in maximising performance during training and competition. It also offers medical personnel the opportunity to reduce health risks in situations where athletes engage in intentional weight loss. Simple non-invasive techniques, including weight monitoring and urine tests, can provide useful information. Bioimpedance methods tend to be easy to use and fairly inexpensive, but generally lack the precision and accuracy necessary for hydration monitoring. Blood tests appear to be the most accurate monitoring method, but are impractical because of cost and invasiveness. Although future research is needed to determine which hydration tests are the most accurate, we encourage sports teams to develop and implement hydration monitoring protocols based on the currently available methods. Medical personnel can use this information to maximise their team's athletic performance and minimise heat- and dehydration-related health risks to athletes.